Visitor Perception-Based Urban Tourism Development in Public Open Space: The Case of Kambang Iwak Park - Randy Rizal; Shinta Oktaviana; Syahidullah Habibie (Universitas Bandar Lampung (UBL), 2026)
This study aims to formulate urban tourism development strategies based on visitor perceptions and SWOT analysis using the IFAS-EFAS approach at Kambang Iwak Park, Palembang. The park possesses historical, ecological, and social values as a public open space with significant potential to be developed as an urban tourism destination. The research employed a quantitative descriptive approach through field observations, literature review, and Guttman-scale questionnaire. The collected data were analyzed using descriptive statistics and SWOT analysis. The findings indicate that the park is positively perceived, particularly in terms of accessibility, comfort, facilities, and overall safety. More than 80% of repondents considered the main facilities to be comfortable and easily accessible. However, several weaknesses remain, particularly regarding personal security, environmental cleanliness, sanitation, and the management of informal activities. The SWOT analysis reveals that the park possesses strong internal strengths and substantial external opportunities to be developed as a family-oriented urban tourism destination. Priority development strategies include strengthening formal security systems, revitalizing lake and public toilet cleanliness, regulating informal activities, organizing regular tourism events, and enhancing sustainable tourism promotion.